Eksplorasi Kuliner Khas Sulawesi Es Pisang Ijo dalam Body Painting pada Gelar Karya Mahasiswa Kecantikan - Andita Erlisa Fitriani; Trisnani Widowati; Novia Restu Windayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of local culture-based makeup art and the exploration of traditional culinary arts in the visual arts play a crucial role in preserving cultural identity while encouraging creative innovation amidst changing times. This study aims to explore the visual representation of the traditional culinary dish, Es Pisang Ijo (green banana ice) and the cultural values ​​of Mallabiri in body painting works based on aesthetics and cultural significance. A practice-led research approach was used, integrating the creative process as part of the research, along with assessments by three professional experts to ensure objectivity. The analysis was conducted using descriptive qualitative and quantitative methods. The results showed that all indicators were in the